Design and Construction of a Biogas Digester for Producing Methane from Cow Dung - Nnadikwe Johnson; Khama Rieborue Emmanue; IKputu Woyengikuro Hilary; Amaefule Chibunma Vivian (Journal Majelis Paspama, 2026)
The increasing demand for renewable energy and the need for sustainable waste management necessitated this study on the design and construction of a biogas digester for producing methane from cow dung. The objectives were to design a mini floating-drum biogas digester, construct and operate the system using cow dung as substrate, evaluate its performance based on biogas volume and methane content, and assess the digested slurry as organic fertilizer. The digester was constructed using locally available materials and consisted of a digestion chamber, inlet and outlet pipes, a water-jacket seal, and an inverted floating drum as gas holder. The system was charged with cow dung slurry mixed at a 1:1 ratio with water and operated under ambient conditions for a retention period of 30 days. Results showed that biogas production commenced on day 3 and reached a peak between day 14 and day 18. A total cumulative biogas yield of 1.26 m³ was recorded, with an average daily production of 0.042 m³. Gas analysis revealed a methane content of 61.4%, carbon dioxide 34.8%, and trace amounts of hydrogen sulfide, hydrogen, nitrogen, oxygen, and water vapor. The methane content was sufficient for combustion, confirming the biogas as methane-rich. The digested slurry obtained was odorless and suitable for use as organic fertilizer. The study concluded that the floating-drum biogas digester is effective for converting cow dung to methane and organic fertilizer under local conditions. The design is simple, cost-effective, and can be adopted by small-scale farms and households for waste management and renewable energy generation. It is recommended that further work focus on gas purification and scale-up for community use.